Observações sobre atividade de mosquitos Culicidae em matas primitivas da planície e perfis epidemiológicos de vários ambientes no Vale do Ribeira, São Paulo, Brasil Observations on mosquito activity in primitive rain forests on plains, and epidemiological profiles for several environments in the Ribeira Valley, S.Paulo, Brazil - Oswaldo Paulo Forattini; Almério de Castro Gomes; Délsio Natal; Jair Lício Ferreira Santos (Universidade de São Paulo, 1986)
Observou-se o ciclo diário da atividade culicídea em ambiente primitivo das florestas perenifólias higrófilas da planície, compreendendo tanto a quaternária como a de transição, do Sistema da Serra do Mar, no Vale do Ribeira, Estado de São Paulo (Brasil). Em cada floresta foram realizadas capturas mensais de 25 horas ininterruptas com o emprego de isca humana, bem como a utilização de armadilha tipo Shannon operadas dentro e fora do ambiente florestal. Registrou-se a dominância de An. cruzii embora não de maneira tão acentuada quanto a verificada na mata da encosta, mas que se manteve durante todos os meses do ano. Juntamente com Ae. serratus e An. bellator, esse mosquito manteve-se continuamente em atividade, na isca humana, durante todo o período das 24 horas. Cx. sacchettae e Ps. ferox revelaram ciclo nictimeral caracteristicamente noturno para o primeiro e diurno para o segundo. A influência crepuscular evidenciou-se com a ocorrência de nítidos picos endocrepusculares para An. cruzii, An. bellator e o caráter eocrepuscular para Cx. sacchettae. Aquelas duas espécies de Kerteszia confirmaram a presença de ritmo paracrepuscular. O Ae. scapularis ocorreu nas coletas efetuadas no aberto, ou seja, no meio extraflorestal onde não se registrou a presença de Ae. serratus. Comparando-se os resultados destas observações com aqueles obtidos no ambiente modificado e na mata da encosta, pôde-se traçar o perfil culicídeo dos quatro locais notando-se a ocorrência de nítida sucessão na fauna, conseqüente às alterações introduzidas pelo homem. Ae. scapularis e Cx. ribeirensis mostraram capacidade de adaptação ao ambiente humano, com a conseqüente importância epidemiológica que desse fenômeno se pode deduzir. Monthly 25-hour catches of Culicidae mosquitoes were carried out at ground level with human bait, in two primitive rain forests on plains in the Ribeira Valley, S.Paulo, Brazil. Regular simultaneous catches were made too, with Shannon traps, both within and outside wooded environments, which included quaternary and transitional forests on plains. Results obtained are presented and discussed. The An. cruzii dominance, though present, was not so remarkable as in the highland forest, previously reported on another work (1986). Nevertheless this mosquito, together with Ae. serratus and An. bellator, showed uninterrupted daily activity with regard to human bait, but with a marked increase at night for the two Kerteszia species. Both these anophelines showed a very clear peak of biting activity at the dusk crepuscular period, sustained in a significant manner outside the forest environments. At the dawn crepuscular period these two mosquitoes showed a peak too. For both crepuscular periods the occurrence of paracrepuscular rhythms including a secondary peak which immediately follows, was confirmed at the two investigation sites. Day-time activity was shown by Sabetini and Ps. ferox, while a nocturnal one was markedly shown by Cx. sacchettae with a clear eocrepuscular rhythm. Even though Ae. scapularis was not a dominant species within the forest, it was collected in significant quantity with the Shannon trap outside the quaternary forest on the plain, while Ae. serratus was found only inside woods. These results allow a comparison with others previously published in 1981 and 1986 and obtained in different Ribeira Valley environments. So it has been possible to describe culicid fauna profiles for three primitive forests, that is to say one on the highland and two on the plain, beside the patch one remaining as extensively modified land for agricultural purposes. The results showed a culicid faunistic succession where the former dominance of An. cruzii, Cx. sacchettae, An. bellator and Ps. ferox in the primitive forest environments was replaced by that of Ae. serratus, Ae. scapularis and Cx. ribeirensis. Besides this, only the two last of these were collected outside a forest environment on the modified land. So this finding allows one to draw conclusions as to the epidemiological importance of An. cruzii in primitive environments and of Ae. scapularis and Cx. ribeirensis in modified ones.